Fenomena Membuka Aib Suami Di Sosmed Dalam Perspektif Hadis - Fatimatuz Zahro; Nasrulloh; Ahmad Nur Fauzi (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
Social media is currently a means of expressing oneself, many people pour their hearts out on social media. However, there are some people who abuse social media. One of them is the wives whose intention is to confide but end up spreading their husband's disgrace on social media. The purpose of writing this article is whether a wife who spreads her husband's disgrace is nusyuz and then reviewed using a hadith perspective. The method in this research is descriptive qualitative by examining what the law is if a wife commits nusyuz. The nusyuz referred to in this research is a wife who spreads her husband's disgrace on social media. The results of this research are that if the disgrace that is spread is true then the solution is communication between the two without having to vent on social media. Introspecting each other, the husband advises the wife not to spread disgrace and the wife advises not to repeat her mistakes for the sake of household harmony. Meanwhile, if the spread of disgrace is not true then it is slander. And the wife is included in the nusyuz category, the nusyuz hadith in this study explains what punishments can be given if the wife is nusyuz, namely being given advice, separating the bed or not having sex with her or finally being beaten but not harming the wife.